THE ANALYSIS OF LONG-TERM OUTCOMES AND ADHERENT TO TREATMENT IN PATIENTS AFTER MYOCARDIAL INFARCTION: KHABAROVSK REGISTER DATA - I. M. Davidovich; L. N. Malay; N. P. Kutishenko (Klinicist, 2017)
Objective. To evaluate the long-term outcomes and medical treatment in patients during 2.5 years after reference acute myocardial infarction (AMI), to study adherent to medical treatment and the role of various factors affecting the long-term prognosis.Materials and methods. The AMI Register included data about all patients, whom are consistently hospitalized in the regional vascular center (RVC) of Khabarovsk during the period from 01.01.14 till 31.03.14. The 2.5 years outcomes and adherence to treatment were evaluated by using phone interview.Results. According to prospective part of the AMI Register of 292 patients discharged from the regional vascular center (RVC), the vital status in 2.5 years managed to be established at 274 (93.8 %) from which died 45 (16.42 %, or 15.40 % from all discharged patients). In structure of a mortality the proportion of dead from cardiovascular disease (СVD) patients made 86.6 %. The long-term mortality of patients with myocardial infarction with ST-segment elevation was 19.3 %, the myocardial infarction non-ST-segment elevation – 13.2 %; р = 0.632.The new predictors of death 2.5 years after the onset of AMI were cerebrovascular diseases, the absence of the antihypertensive drugs and β-blockers before reference AMI, not prescribing antiplatelet drugs in loading doses in the early hours of the disease. Frequency of real reception of statins was 65.1 %, angiotensin-renin blockers –76.0  %, β-blocker – 73.8 % of patients after AMI. Only 55.9 % patients Received double antithrombocytic therapy (DATT)  during a year. By  the Moriscors–Green test adherent were only 109 (47.6 %). 79 (34.5 %) know their values cholesterol, blood pressure and blood glucose.Conclusions. Indicators of the remote lethality among patients authentically didn’t differ with a myocardial infarction with ST-segment elevation in AMI and a myocardial infarction non-ST-segment elevation in AMI in the remote period. The register AMI taped failure predictors, showed the insufficient frequency of reception of recommended medicinal drugs in secondary prophylaxis after a referent AMI, especially concerning statines and DATT.  The  commitment of patients of long medicamental therapy, and also awareness on indicators of quality of treatment (level of a cholesterin, blood pressure) in real clinical practice according to the register were low.